2021
DOI: 10.1016/j.foodpol.2021.102104
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a health risk ‘signalling effect’ following the introduction of a sugar-sweetened beverage tax

Abstract: Highlights Sugar-sweetened beverage (SSB) taxes may signal information about health risks. Risk signals may be undermined by public misperception of taxed products. Industry may produce “countersignals” through advertising. Policymakers can amplify positive signalling effects to maximize health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This could potentially lead to underestimation of differences in tax effects if there was regional pricing of beverages by chain PLOS GLOBAL PUBLIC HEALTH retailers, for example. San Jose ´may also have shared the "risk signaling" effect of the Bay Area SSB tax measures [50]. Cawley and Frisvold found greater difference-in-differences using a broader synthetic national control than controls in areas adjacent to taxing cities [22].…”
Section: Limitationsmentioning
confidence: 99%
“…This could potentially lead to underestimation of differences in tax effects if there was regional pricing of beverages by chain PLOS GLOBAL PUBLIC HEALTH retailers, for example. San Jose ´may also have shared the "risk signaling" effect of the Bay Area SSB tax measures [50]. Cawley and Frisvold found greater difference-in-differences using a broader synthetic national control than controls in areas adjacent to taxing cities [22].…”
Section: Limitationsmentioning
confidence: 99%
“…The 'signaling effect' mechanism suggests that the publicizing and adoption of taxes with associated price increases of taxed foods and beverages communicates to consumers that these products are inferior to untaxed products. Awareness of health risks associated with their consumption may influence consumers to reduce purchases (14, 15,24,34,35,44,45). Two studies reported that signaling effects from taxes were amplified by information campaigns that may have increased awareness of the health risks associated with calorie-dense foods and beverages that are high in sugar, fat or salt (35,46).…”
Section: Design and Implementation Considerationsmentioning
confidence: 99%
“…Introducing a tax based on sugar content (larger tax for SSB higher in sugar) might also help decrease sugar intake, especially by encouraging SSB manufacturers to reduce the sugar content of their products (43) . Tax introduction or updates are also an opportunity to effectively communicate the detrimental effects of SSB on health (9,44) or raise revenues to fund public health or social programmes (45) . Large taxes on SSB should also come with subsidies for healthy foods to limit tax financial regressivity on low-income households (46) .…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Following taxation, soda substitution towards 100 % fruit juices (untaxed in 6/6 countries, Table 1) and artificially sweetened beverages (taxed in 5/6 countries, but at lower rate in 2/5 countries) was likely. While substitution towards water (18,19) would be beneficial in terms of obesity prevention, substituting sodas with other sugary drinks (1,28,44) would produce little health benefits.…”
Section: Strengths and Limitationsmentioning
confidence: 99%